2020
DOI: 10.1002/ece3.6399
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral constraints on local adaptation and counter‐gradient variation: Implications for climate change

Abstract: Resource allocation to growth, reproduction, and body maintenance varies within species along latitudinal gradients. Two hypotheses explaining this variation are local adaptation and counter‐gradient variation. The local adaptation hypothesis proposes that populations are adapted to local environmental conditions and are therefore less adapted to environmental conditions at other locations. The counter‐gradient variation hypothesis proposes that one population out performs others across an environmental gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
(65 reference statements)
3
5
0
Order By: Relevance
“…However, at 26.5 ∘ C, we found that breeding pairs produced smaller broods when compared to the baseline treatment (26 ∘ C) but found no effect of temperature on individual offspring size. Brood size regulation in response to thermal cues has been documented for Nicrophorus orbicollis (Quinby et al, 2020). Consistent with our findings, this species was found to produce smaller broods at higher temperatures, however, individual offspring size (measured in mass) decreased at higher temperatures.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, at 26.5 ∘ C, we found that breeding pairs produced smaller broods when compared to the baseline treatment (26 ∘ C) but found no effect of temperature on individual offspring size. Brood size regulation in response to thermal cues has been documented for Nicrophorus orbicollis (Quinby et al, 2020). Consistent with our findings, this species was found to produce smaller broods at higher temperatures, however, individual offspring size (measured in mass) decreased at higher temperatures.…”
Section: Discussionsupporting
confidence: 92%
“…Reduced reproductive success at temperatures exceeding 27 ∘ C has been observed in other burying beetles species (Quinby et al, 2020) and could represent a byproduct of the physiological constraints imposed by thermal stress. However, when exposed to low and high thermal extremes, there is evidence that burying beetles are less likely to initiate reproduction in temperature extremes represented within their native environment (Quinby et al, 2020). The extremely low reproductive success rates documented for N. marginatus at 27.5 ∘ C could represent a behavioural strategy employed to avoid a costly reproductive event in an aversive environment.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Nicrophorus species showing that burying beetles are unlikely to initiate breeding in extreme environmental conditions (Quinby et al, 2020). Thus, the heatwave most likely delayed the onset of breeding, rather than lengthened the rate of offspring development.…”
Section: Effects Of Heatwaves Occurring During Matingmentioning
confidence: 99%
“…Temperature was chosen as the environmental stressor because of its ecological relevance in the context of climate change. Insects, being poikilothermic, are particularly vulnerable to heat stress, and research on burying beetles specifically has shown that they have reduced breeding success at higher temperatures (Moss & Moore, 2021; Quinby et al, 2020; Sun & Kilner, 2020). We chose to expose the beetles to the temperature treatments during sexual maturation alone because this is the time when an adult beetle’s gonads are developing (e.g.…”
Section: Introductionmentioning
confidence: 99%